Heterogenic Origin of Micro RNAs in Atlantic Salmon (Salmo salar) Seminal Plasma - Bizuayehu, Teshome Tilahun (Int J Mol Sci, 2020)
The origin and contribution of seminal plasma RNAs into the whole semen RNA repertoire are poorly known, frequently being overlooked or neglected. In this study, we used high-throughput sequencing and RT-qPCR to profile microRNA (miRNA) constituents in the whole semen, as well as in fractionated spermatozoa and seminal plasma of Atlantic salmon (Salmo salar). We found 85 differentially accumulated miRNAs between spermatozoa and the seminal plasma. We identified a number of seminal plasma-enriched and spermatozoa-enriched miRNAs. We localized the expression of some miRNAs in juvenile and mature testes. Two abundant miRNAs, miR-92a-3p and miR-202-5p, localized to both spermatogonia and somatic supporting cells in immature testis, and they were also highly abundant in somatic cells in mature testis. miR-15c-5p, miR-30d-5p, miR-93a-5p, and miR-730-5p were detected only in mature testis. miRs 92a-3p, 202-5p, 15c-5p, and 30d-5p were also detected in a juvenile ovary. The RT-qPCR experiment demonstrated lack of correlation in miRNA transcript levels in seminal plasma versus blood plasma. Our results indicate that salmon semen is rich in miRNAs, which are present in both spermatozoa and seminal plasma. Testicular-supporting somatic cells are likely the source of seminal plasma enrichment, whereas blood plasma is unlikely to contribute to the seminal plasma miRNA repertoire.